The Effect of Provincial Minimum Wages and Open Unemployment Rate on Poverty in DKI Jakarta 2016 - 2023 - Cut Nurul Aidha; Safna Afriani; AB Christono (Jurnal Wacana Ekonomi, 2025)
Poverty has always been an interesting issue in research, especially when linked to unemployment and minimum wage levels. The purpose of this study is to examine how the provincial minimum wage and the open unemployment rate affect poverty levels in DKI Jakarta during the period 2016–2023. The data used is secondary quantitative time series data obtained from the DKI Jakarta Central Statistics Agency (BPS) and the Ministry. Republic of Indonesia Labor Force during the period 2016 -2023. The study employs a multiple linear regression model. The findings indicate that, when tested individually, the Provincial Minimum Wage (t-test) shows a significant effect on poverty, as the calculated t-value exceeds the critical value (3.726 > 1.943). In contrast, the Open Unemployment Rate (t-test) demonstrates no significant impact on poverty since the obtained t-value is lower than the critical threshold (1.727 < 1.943). Nevertheless, the joint test (f-test) reveals that both variables collectively exert a significant influence on poverty, supported by the f-value being higher than the f-table (13.291 > 5.79).